2014
DOI: 10.1016/j.aat.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of three methods of ProSeal laryngeal mask airway insertion in children with simulated difficult laryngoscopy using a rigid neck collar

Abstract: PLMA insertion with combined IT and stylet technique was more frequently successful than the digital or IT technique in pediatric patients without cervical spine motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In our study, the application of a neck collar reduced both head and neck movement and mouth opening. Reduced mouth opening has been reported in patients with neck collars [ 11 ]. Reduced neck movement leads to reduced head flexion, which contributes to the worsening of Cormack-Lehane grades with direct laryngoscopy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the application of a neck collar reduced both head and neck movement and mouth opening. Reduced mouth opening has been reported in patients with neck collars [ 11 ]. Reduced neck movement leads to reduced head flexion, which contributes to the worsening of Cormack-Lehane grades with direct laryngoscopy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the insertion techniques can significantly change the ease and success rate of PLMA insertion, time required for effective airway, airway leakage pressure, success rate of nasogastric tube insertion, and incidence of complications. 2 , 3 We believe that addressing this issue would further clarify the transparency of this study.…”
mentioning
confidence: 86%
“…Secondly, in our study, PLMA were inserted digitally. Das et al 3 previously compared 3 PLMA insertion methods in child patients with rigid cervical collars. They performed comparisons between the method combining the stylet and inserter apparatus, a method using the inserter apparatus and the conventional digital insertion method.…”
mentioning
confidence: 99%
“…Several techniques continue to be developed to improve the placement and performance characteristics of PLMA in pediatric patients; the introducer, pharyngoscopy, 90° and 180° rotation technique, partially inflated cuff, suction catheter, and gum elastic bougie technique. [ 2 3 4 5 6 7 ] The correct placement may be more difficult in children due to the relatively larger tongue, a superior larynx with a floppy epiglottis, and the frequent presence of hypertrophied tonsils. [ 7 ] The success rate of inserting LMAs in pediatric patients at the first attempt varies between 67%–92%.…”
Section: Introductionmentioning
confidence: 99%